Remarkable lowering in the synthesis temperature of LiMn 2 O 4 via citrate solution-gel synthesis facilitated by ethanol - Maino, G; Carleer, R; Marchal, W; Bonneux, G; Hardy, A; Van Bael, M K (Dalton transactions : an international journal of inorganic chemistry, 2017)
LiMn O (LMO) is interesting from the viewpoint of its energy storage applications as it is a cathode in lithium ion batteries (LIB), which contains no rare, toxic or expansive elements, while it provides a high theoretical capacity (148 mA h g ) at a reasonable voltage (4 V region) and a higher thermal stability compared to cobalt based cathodes and has a good rechargeability and cycling stability due to its spinel structure. Low temperature synthesis routes for cathode materials are currently gaining attention, in order to decrease the ecological footprint of the final LIB. Here, the crystallization temperature of LMO by a citrate based solution-gel synthesis was significantly lowered, to as low as 250 °C by the addition of ethanol to the precursor. The role of ethanol in this synthesis process was explored. It was found to lead to a considerable increase in the oxidation rate of the redox couple Mn /Mn , a lowering of the precursor decomposition temperature by 200 °C, besides a drastic decrease in the crystallization temperature (reaching 250 °C). Moreover, the main cause was identified to be an esterification reaction of ethanol with the carboxylic acid in the precursor complexes, taking place before the oxide formation. The insights obtained strengthen the knowledge regarding citrato-Mn /Mn complexes present in aqueous solution-gel synthesis routes and are relevant for the preparation of various manganese containing oxides. Moreover, the precursor developed opens up a new possibility for the low temperature synthesis of LMO powders and thin films for application in LIB. In the case of thin film batteries, the low temperature processing provides compatibility with other materials in the thin film battery stack, avoiding undesired oxidations or interfacial reactions.